Radiometric dating of the Ootun palaeosol and its implication for the age of the Shifting Sand in Ngorongoro Lengai Geopark (Arusha, Tanzania) - Makongoro, Mohamed Zengo; Vegi, Maheswara Rao; Vuai, Said Ali Hamad; Msabi, Michael Mwita (Geologos, 2022)
The Shifting Sand is a barchan dune in Ngorongoro Lengai Geopark in Arusha, Tanzania. The geopark, a UNESCO World Heritage Site, is protected by the Ngorongoro Conservation Area Authority. The dune ranks amongst the main geosites that have been attracting numerous tourists; it formed as a result of volcanic ash eruptions that led to tephra deposition on a palaeosol (palaeosurface) in the Ootun area. The easterly winds modified the ash into dunes and headed to the Olduvai Gorge area. The age of the Shifting Sand dune is not known in detail. In the present study, we employ the radiocarbon (14C) dating method to date a subsurface palaeosol bed in the Ootun area where the tephra (i.e., original Shifting Sand materials) was originally deposited. An Accelerator Mass Spectrometer was used to determine the carbon-14 date of the palaeosol so as to estimate the age of the Shifting Sand dune, and an Energy Dispersive X-ray Fluorescent Spectrometer to determine the chemical composition of the Shifting Sand material and the tephra bed for correlative purposes. A radiocarbon (14C) date of 2510 ± 30 years BP for the Ootun palaeosol was obtained to estimate the minimum age of the Ootun subsurface tephra deposited in the area; since then, this started to move westwards towards the Olduvai Gorge area, where it is today defined as the Shifting Sand. The current findings add educational value to the Shifting Sand in Ngorongoro Lengai Geopark and improve our understanding of the eruption history of the Gregory Rift volcanoes.